Tanggung Jawab Hukum Pidana Pelanggaran Otonomi Pasien - Eko Pujiyono (Jurnal Hukum dan Etika Kesehatan, 2022)
Patient autonomy is an important part in maintaining human dignity and in legal engagements in the medical field, patient autonomy is a form of freedom to deal with the patient’s sick condition. The freedom inherent in humans must have an element of responsibility, including patient autonomy inherent in sick people and must be accountable for human values in health services. The purpose of the study is to examine whether violations of the principle of patient autonomy are a form of crime that can be accounted for, with a normative legal research type using a statutory approach and a conceptual approach. Primary legal materials are laws and regulations using legislation and regulations, while secondary legal materials are from reserch results, journals and legal books. The result of the research is that the laws and regulations in the field of hospital and medical have not explicitly regulated the violation of the principle of autonomy as a criminal act because in the Criminal Code, the Medical Practice Law, the Hospital Law does not explicitly formulate punishment in the event of a violation of patient autonomy. Criminal liability by doctors in the Criminal Code does not have a causal correlation between unlawful nature and criminal responsibility forviolations of patient autonomy, so the search for causality is fundamental in determining the elements of unlawful nature and criminal responsibility. The application of offense articles in the Criminal Code needs to be avoided on the basis of special considerations for the application of health law because it contains health ethics with moral characteristics.